Dakwah di Kalangan Anak Muda: Menjaga Identitas Islam di Era Digital - Dinda Ayu Triani; Mumtaz Ali Ridha Al Munawar; Rahma Amelia; Syahla Aulia Syahida; Zahra Nabilatu Azkia; Edi Suresman (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2025)
The development of digital technology has brought significant changes to various aspects of life, including the dissemination of Islamic preaching. Social media and digital platforms have become the primary sources for young people to access Islamic information, whether from credible sources or unreliable ones. On one hand, digital preaching presents a great opportunity to convey Islamic teachings in a more creative and innovative way through various platforms such as YouTube, Instagram, TikTok, and podcasts. However, on the other hand, challenges also arise, such as the spread of inaccurate information and difficulties in distinguishing valid sources. This study employs a descriptive qualitative method with a phenomenological approach to understand the experiences of young people in accessing digital preaching and how they maintain their Islamic identity in the digital era. Data was collected through in-depth interviews with Muslim youth who actively engage with digital preaching, as well as literature reviews of various related studies. The findings indicate that digital preaching has a positive impact on enhancing young people’s understanding of Islam, particularly when presented in a manner that aligns with their characteristics. However, challenges remain in filtering accurate information and dealing with the broader influence of the digital world. This article discusses the effectiveness of digital preaching in shaping the Islamic identity of young people, the challenges involved, and the strategies that can be applied to make preaching more relevant and effective in guiding the younger Muslim generation. This study is expected to contribute to the development of more adaptive preaching strategies in the digital era.